Which therapeutic exercise is most effective for improving ankle inversion muscle function in individuals with chronic ankle instability? A systematic review and network meta-analysis - Zhang, Haipeng; Luan, Lijiang; Shi, Xiaojian; Tan, Jingwang; Adams, Roger; Wang, Hong; Han, Jia (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study was conducted to investigate the effects of diverse therapeutic exercise regimens on enhancing ankle inversion muscle function in individuals with chronic ankle instability (CAI).MethodsA systematic search was performed across five international electronic databases (e.g., PubMed, Cochrane Library, Embase, Web of Science, and EBSCO) from their inception to December 2024. Randomized controlled trials focusing on the keywords “ankle instability,” “exercise therapy,” and “muscle strength” was screened. Data extraction and quantitative analysis were subsequently executed. Methodological quality and risk of bias were assessed with Cochrane Collaboration Bias Risk Assessment Tool.ResultsNine studies involving 366 participants were included in the network meta-analysis (NMA). The findings demonstrated that all therapeutic exercise modalities (neuromuscular training (NT), (Effect size (ES) = 1.05; 95%CI = 0.29–1.82), strength training (ST), (ES = 1.36; 95%CI = 0.73–1.99), combined neuromuscular and strength training (NST), (ES = 2.82; 95%CI = 1.89–3.74) and combined neuromuscular and whole-body vibration training (NWBVT), (ES = 1.92; 95%CI = 0.62–3.22) exhibited statistically superior efficacy compared to control groups. Surface Under the Cumulative Ranking Curve (SUCRA) probability rankings identified NST as the intervention with the highest likelihood of optimal efficacy (99.9%). ST (64.6%) alone demonstrated a significant advantage over NT alone (45.9%). Conversely, NWBVT was associated with the lowest therapeutic probability (38.9%).ConclusionCombined neuromuscular and strength training (NST) constitutes the most effective therapeutic exercise for augmenting ankle inversion muscle function in CAI populations. Compared to isolated NT or ST interventions, the integration of these modalities demonstrates greater efficacy in addressing functional impairments in CAI individuals.